Slicing silicone neonatal vascular catheter tips improves colonization detection by the roll-plate technique. (June 2017) - Guembe, M.; Martín-Rabadán, P.; Cruces, R.; Pérez Granda, M.J.; Bouza, E.
Abstract: Objective: Silicone neonatal peripherally inserted central catheters (SN-PICCs) are a common cause of catheter-related bloodstream infection (C-RBSI) in neonates. Our objective was to compare the yield of traditional roll-plate technique (TRP), roll-plate after slicing (RPS), and sonication after slicing (SS) for the detection of colonization and C-RBSI in SN-PICCs. Methods: We prospectively cultured tips from SN-PICCs withdrawn from paediatric patients admitted to our institution with suspicion of infection. We first cultured the catheter tip using TRP and then divided the catheter into two segments. RPS was performed by longitudinally slicing one segment and the fragments were cultured. SS was performed by transversally slicing the other segment followed by culture after sonication. We calculated the validity values of each technique individually by comparing them with the diagnostic standard of colonization and C-RBSI. Results: We included 162 SN-PICCs, 46 of which were colonized. Sensitivity rates for colonization and C-RBSI with TRP, RPS and SS were, respectively, 71.7%, 80.4% and 67.4%; and 74.2%, 90.3% and 77.4%. Conclusion: Catheter slicing should be performed before the roll-plate technique to ensure optimal diagnosis on SN-PICCs.